Development of a digital output temperature probe for precision measurements - (:unkn) unknown (Geothermal Resources Council, 2015)
Electrical wireline methods are generally used for precision temperature-depth measurements. In general, four-wire transmission cables are used for eliminating the cable resistance effects. These systems are vulnerable due to the requirements of keeping the cable integrity against breakdown of the electrical insulation. A digital output temperature probe allows using a mono-wire data transmission cable thus increasing the cable integrity. We report the design and the early test results of a digital output temperature probe. © Copyright (2015) by Geothermal Resources Council All rights reserved.
Keywords: Exploration; Geophysics; Temperature logging; Tool development; Well logging